Advanced Thermoelectric Materials for Energy Harvesting Applications - Memon, Saim (IntechOpen, 2019)
Advanced Thermoelectric Materials for Energy Harvesting Applications is a research-intensive textbook covering the fundamentals of thermoelectricity and the process of converting heat energy into electrical energy. It covers the design, implementation, and performance of existing and advanced thermoelectric materials. Chapters examine such topics as organic/inorganic thermoelectric materials, performance and behaviors of thermoelectric devices, and energy harvesting applications of thermoelectric devices.